1996
DOI: 10.1146/annurev.micro.50.1.513
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Adhesion by Oral Bacteria

Abstract: Adherence to a surface is a key element for colonization of the human oral cavity by the more than 500 bacterial taxa recorded from oral samples. Three surfaces are available: teeth, epithelial mucosa, and the nascent surface created as each new bacterial cell binds to existing dental plaque. Oral bacteria exhibit specificity for their respective colonization sites. Such specificity is directed by adhesin-receptor cognate pairs on genetically distinct cells. Colonization is successful when adherent cells grow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
274
0
16

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(295 citation statements)
references
References 216 publications
5
274
0
16
Order By: Relevance
“…Such physical and chemical interactions are important when considering the development of dental-plaque biofilms because both Streptococcus gordonii and Streptococcus oralis are indigenous commensal species that are among the first to colonize clean tooth surfaces (Aas et al, 2005;Diaz et al, 2006;Nyvad & Kilian, 1987;Socransky et al, 1977). S. gordonii and S. oralis belong to a genus that has been referred to as containing 'pioneering colonizers' (Kolenbrander et al, 1990) and these species are consistently isolated from dental-plaque biofilm communities, albeit at different relative amounts (Nobbs et al, 2009;Paster et al, 2006;Whittaker et al, 1996). The two species coaggregate with each other and numerous other oral species through complex adhesin-receptor mechanisms (Kolenbrander et al, 2002;Nobbs et al, 2009) and both have also recently been demonstrated to produce AI-2 (Blehert et al, 2003;McNab et al, 2003;Rickard et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such physical and chemical interactions are important when considering the development of dental-plaque biofilms because both Streptococcus gordonii and Streptococcus oralis are indigenous commensal species that are among the first to colonize clean tooth surfaces (Aas et al, 2005;Diaz et al, 2006;Nyvad & Kilian, 1987;Socransky et al, 1977). S. gordonii and S. oralis belong to a genus that has been referred to as containing 'pioneering colonizers' (Kolenbrander et al, 1990) and these species are consistently isolated from dental-plaque biofilm communities, albeit at different relative amounts (Nobbs et al, 2009;Paster et al, 2006;Whittaker et al, 1996). The two species coaggregate with each other and numerous other oral species through complex adhesin-receptor mechanisms (Kolenbrander et al, 2002;Nobbs et al, 2009) and both have also recently been demonstrated to produce AI-2 (Blehert et al, 2003;McNab et al, 2003;Rickard et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Considerable information is known regarding the adhesion and coaggregation of oral bacteria in plaque development (8,41), but little is known of the proteins involved in initial attachment of oral bacteria to surfaces. Using a microtiter plate assay, biofilms of the early colonizer of the dentition, Streptococcus gordonii, were grown for 16 h. Biofilm-defective mutants generated by transposon mutagenesis were identified, and the genes inactivated included those associated with osmoregulation, adhesion, nutrient sensing, and quorum sensing (comD) (22).…”
mentioning
confidence: 99%
“…Pode aderir-se a fibroblastos, células epiteliais, eritrócitos, fibronectina e à hidroxiapatita coberta por saliva 5,6,18 . Tem sido demonstrado que o T. denticola pode invadir células e tecidos 5,18 , além de induzir a desgranulação de leucócitos polimorfonucleares e o aumento da produção de colagenase, gelatinase e elastase. Esta espiroqueta também apresenta atividade hemolítica, imunossupressora e algumas cepas expressam em sua superfície proteínas com atividade citotóxica e de adesão.…”
Section: Discussionunclassified